First-Principles Study on the Structural and Electronic Properties of N Atoms Doped-Rutile TiO2 of Oxygen Vacancies - Zhong-Liang Zeng (Advances in Materials Science and Engineering)
For the propose of considering the actual situation of electronic neutral, a simulation has been down on the basis of choosing the position of dual N and researching the oxygen vacancy. It is found that the reason why crystal material gets smaller is due to the emergence of impurity levels. By introducing the oxygen vacancy to the structure, the results show that while the oxygen vacancy is near the two nitrogen atoms which have a back to back position, its energy gets the lowest level and its structure gets the most stable state. From its energy band structure and density, the author finds that the impurity elements do not affect the migration of Fermi level while the oxygen vacancy has been increased. Instead of that, the conduction band of metal atoms moves to the Fermi level and then forms the N-type semiconductor material, but the photocatalytic activity is not as good as the dual N-doping state.